MAINTAINING JOINT MOBILITY IN THE CRITICAL SICK: CASE STUDY - Ana Bernardo Beliz; Maria José Bule; Luís Manuel Mota De Sousa (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Background: Immobility in critically ill patients is conditioned by the condition of the disease or by the effect of drugs, but in both cases, it emerges as a problem from the perspective of functional recovery. The decrease in muscle mass and joint amplitude delay or hinder the processes of recovery from spontaneous ventilation and self-care. When bed rest is required, safe rehabilitation nursing care is a resource to mitigate the problems associated with immobility. Objective: Evaluate the results of rehabilitation nursing care after the application of a structured passive joint mobilization care intervention in critically ill patients. Methods: Qualitative study, case study type. The case of an adult person in a critical situation is presented and eight joint mobilization sessions were carried out by a rehabilitation nurse. Joint amplitude was evaluated using goniometry before and after the application of a rehabilitation program. Study approved by the ethics committee. Results: It was found that in 26 days of admission to the intensive care unit, the joint amplitude remained in the different segments and there were gains in the supination movements of the forearm, left hand extension and right knee flexion. Passive joint mobilization exercises did not interfere with the stability of physiological parameters or adaptation to the ventilatory prosthesis. Conclusion: The results reveal that there is no decrease in joint amplitude and are sensitive to rehabilitation nursing care, in a structured and regular mobilization plan. There were gains in health and the minimization of complications associated with immobility. Other studies should be carried out in order to parameterize not only the intervention plan but also the evidence of the results obtained.